Die Allgemeinverbindlicherklärung im Tarifvertragssystem: Wirkung und Bedeutung der Reform von 2014 - Sandra Vogel (Institut der deutschen Wirtschaft (IW), 2019)
Neben einer rechtlichen Einordnung sogenannter Erstreckungsmechanismen wurden hierzu soziologische und ökonomische Forschungsarbeiten ausgewertet und um qualitative Ergebnisse aus Experteninterviews ergänzt. Es zeigt sich, dass die 2014er-Reform bisher nicht zu mehr Allgemeinverbindlicherklärungen oder der Einbindung vieler neuer Branchen geführt hat. Ebenso wenig ist die Tarifbindung in Deutschland seitdem gestiegen. Vielmehr legen die Ergebnisse nahe, dass auf einen umfassenden Einsatz der AVE verzichtet und ihr Einsatz jeweils im Einzelfall vor dem Hintergrund der branchenspezifischen Gegebenheiten geprüft werden sollte. So können AVE mit Freerider-Effekten einhergehen und Anreize für Unternehmen beziehungsweise Beschäftigte schwachen, freiwillig Mitglied in einem Arbeitgeberverband oder in einer Gewerkschaft zu werden. Starke Tarifvertragspartner sind jedoch Voraussetzung für das Gelingen der Tarifautonomie. Und so ist es Aufgabe der Tarifvertragsparteien und nicht des Staates, die tarifliche Ordnung von innen heraus zu starken, indem sie Tarifvertrage abschließen, die für möglichst viele Unternehmen und Beschäftigte in den einzelnen Branchen attraktiv sind. – – With collective bargaining coverage in decline, the summer of 2014 saw new rules come into force designed to make it easier to extend collective bargaining agreements to all establishments in a given sector and region regardless of their affiliation to the bargaining parties. This IW Analysis examines whether the objectives of the 2014 reform have been achieved and undertakes a general assessment of the effects of increasing the use of such declarations (in German Allgemeinverbindlicherklärungen or AVEs). In addition to a legal classification of extension mechanisms of this kind, a review of sociological and economic research was conducted and supplemented by qualitative information from expert interviews. The results show that the 2014 reform has as yet led neither to more AVE declarations nor to the inclusion of many new industries. Specifically, it has failed to broaden collective bargaining coverage in Germany. Indeed, the results rather suggest that widespread resort to AVEs should be abandoned and that their use should be considered on a case-bycase basis in the light of circumstances in specific industries. This is because AVEs can give rise to freerider effects and weaken the incentives for companies and their workforces to become voluntary members of an employers' association or trade union. Yet strong collective bargaining partners are essential if Germany's collective bargaining autonomy is to function successfully. It is thus the responsibility of the bargaining parties, and not the state, to strengthen the collective wage bargaining system from within by concluding agreements in the individual sectors that are attractive to as many companies and employees as possible.
Keywords: 330